Linking food, nutrition and the environment in Indonesia: A perspective on sustainable food systems - Nurhasan, M.; Samsudin, Y.B.; McCarthy, J.F.; Napitupulu, L.; Dewi, R.; Hadihardjono, D.N.; Rouw, A.; Melati, K.; Bellotti, W.; Tanoto, R.; Campbell, S.J.; Ariesta, D.L.; et al. (Center for International Forestry Research, 2021)
This brief reviews the interlinkages between food, nutrition and the environment in Indonesia, and the role of national food policies in addressing the challenges in these sectors.